A Short‐Step Synthesis of 1, 6‐Methano[10]annulene‐3, 4‐dicarboximides and Their Benzene‐, Naphthalene‐, and Thiophene‐Annulated Compounds. Issue 27 (28th July 2014) - Oda, Mitsunori; Nakamura, Tomomi; Neha, Miyako; Miyawaki, Daisuke; Ohta, Akira; Kuroda, Shigeyasu; Miyatake, Ryuta
Abstract: Triphenylphosphorane reagents8 react with 1, 3, 5‐cycloheptatriene‐1, 6‐dicarbaldehyde (2 ) under acidic as well as basic conditions to produce 1, 6‐methano[10]annulene‐3, 4‐dicarboximides1 in moderate ‐to‐ good yields. The reagents8 react with 3, 4‐arene‐annulated 1, 3, 5‐cycloheptatriene‐1, 6‐dicarbaldehydes9, 10, and11 to afford only the Wittig condensation products under acidic conditions but produce the arene‐annulated annulenedicarboximides under basic conditions. The structures of some of the dicarboximides and the intermediate Wittig condensation products were determined by X‐ray structural analysis. The emission properties of the dicarboximides were also studied. Abstract : A new one‐pot procedure for 1, 6‐methano[10]annulene‐3, 4‐dicarboximides and its arene‐annulated compounds is developed. Cyclohepta‐1, 3, 5‐triene‐1, 6‐dicarbaldehyde and its arene‐annulated dicarbaldehyde analogs react with various phosphorane reagents to give 1, 6‐methano[10]annulene‐3, 4‐dicarboximides.